Experimental and Mathematical Study of the Capillary Effect in Microflow Inside Polypropylene Hollow Fiber Tubes (Journal of Engineering, 2025)
Polypropylene (PP) capillary microtubes hold strong potential for use in advanced liquid cooling systems, but their internal flow behavior remains insufficiently understood. Critical factors—such as capillarity, flow regime, and pressure drop—directly influence their thermal performance and practical applicability. Despite their relevance, detailed studies on these parameters in PP hollow fiber microtubes are lacking. This study addresses that gap through a combined mathematical and microscopic investigation of water flow inside PP microtubes with a 0.6 mm inner diameter. Results show that capillary effects are negligible across all tested conditions, contributing only ~0.2% to ~2.7% to the total pressure drop. Moreover, capillary pressure remained largely unaffected by changes in water temperature. The extremely low Knudsen number (~4×10⁻⁷) confirms continuum flow behavior, justifying the use of classical models like the Reynolds analogy. These findings deepen our understanding of flow dynamics in PP microtubes and support their integration into micro-scale thermal management systems.